X*(2x+3)-x=3x+5

Simple and best practice solution for X*(2x+3)-x=3x+5 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for X*(2x+3)-x=3x+5 equation:



X(2X+3)-X=3X+5
We move all terms to the left:
X(2X+3)-X-(3X+5)=0
We add all the numbers together, and all the variables
-1X+X(2X+3)-(3X+5)=0
We multiply parentheses
2X^2-1X+3X-(3X+5)=0
We get rid of parentheses
2X^2-1X+3X-3X-5=0
We add all the numbers together, and all the variables
2X^2-1X-5=0
a = 2; b = -1; c = -5;
Δ = b2-4ac
Δ = -12-4·2·(-5)
Δ = 41
The delta value is higher than zero, so the equation has two solutions
We use following formulas to calculate our solutions:
$X_{1}=\frac{-b-\sqrt{\Delta}}{2a}$
$X_{2}=\frac{-b+\sqrt{\Delta}}{2a}$

$X_{1}=\frac{-b-\sqrt{\Delta}}{2a}=\frac{-(-1)-\sqrt{41}}{2*2}=\frac{1-\sqrt{41}}{4} $
$X_{2}=\frac{-b+\sqrt{\Delta}}{2a}=\frac{-(-1)+\sqrt{41}}{2*2}=\frac{1+\sqrt{41}}{4} $

See similar equations:

| 9+10=x-3 | | 4x=1/2(9x+26-35) | | 6^x=22 | | 3/8w=77/8 | | .7m=6.3 | | 4x+20+2(x–7)=0 | | 5b+12=52 | | 2/3y+3=11 | | 15x=12x+16 | | 2+4+4x15= | | 2x-3(x-2)+8=7 | | 25x-200=3350 | | 5(x+3)=2(5x-5) | | 2x+5x=6x-2x | | 122x*x=x | | -5=x-(-4) | | 0x-x=x | | 4x-(2x-x)=9 | | 8.8^2x=90 | | 6(x-11)=2(3x+8 | | 3(y+6)=8y+15.5y | | 2x+13+6(x-5)=0 | | x-(.2x)=18 | | -3x^2+×^3=4x | | 8x−22=−70 | | -3+8(x-2)=15x+5-7x | | 7(x+3)=4x-3 | | x+3/4+5(7x+9)/3=3(4x+3)/12-7/2 | | -6(x)-7=-1(-9+2x | | x-2/3=4x | | 8x-2(x-5)=(x-1) | | 5x/2+1=4-2(x/3+3/4 |

Equations solver categories